A near-infrared fluorophore for live-cell super-resolution microscopy of cellular proteins. - Lukinavičius, G; Umezawa, K; Olivier, N; Honigmann, A; Yang, G; Plass, T; Mueller, V; Reymond, L; Corrêa, I; Luo, Z; Schultz, C; Lemke, E; et al. (2013)
The ideal fluorescent probe for bioimaging is bright, absorbs at long wavelengths and can be implemented flexibly in living cells and in vivo. However, the design of synthetic fluorophores that combine all of these properties has proved to be extremely difficult. Here, we introduce a biocompatible near-infrared silicon-rhodamine probe that can be coupled specifically to proteins using different labelling techniques. Importantly, its high permeability and fluorogenic character permit the imaging of proteins in living cells and tissues, and its brightness and photostability make it ideally suited for live-cell super-resolution microscopy. The excellent spectroscopic properties of the probe combined with its ease of use in live-cell applications make it a powerful new tool for bioimaging.